PENGARUH BEBERAPA KONSENTRASI GARAM PADA BEBERAPA VARIETAS PADI LOKAL PASANG SURUT DI KABUPATEN INDRAGIRI HILIR - nursida, nursida; Yoyon Riono (Fakultas Pertanian, Program Studi Agroteknologi, 2023)
Abstract Research to determine the effect of several salt concentrations on several tidal local rice varieties in Indragiri Regency. The research was conducted in the wire house of the Faculty of Agriculture from March to June 2020. This research used a completely randomized factorial design with 2 treatment factors, namely variety and salt concentration. The variety factor consisted of the Frog, Lemongrass, Karya, Arum and Super varieties. The salt concentration factor consisted of 0 nM, 100 nM, 200 nM and 300 nM. IR 64 which is salt sensitive is used as a control variety. All varieties of rice were sown in tarpaulins with mud as the medium. Rice seeds that are 14 days old are transferred to polybags. Rice is watered with tap water twice per day for two weeks. After two weeks of watering, the rice was then flushed with NaCl according to the treatment twice per day. Salt watering was stopped when one of the lines died (salt sensitive lines) then continued with watering with tap water twice per day for two weeks. The influence of the salt concentration given to the Serai variety showed that leaf width, number of tillers and root length were quite tolerant at concentrations of 100 – 300 nM, while the Super variety produced smaller number of tillers, leaf width and root length compared to other treatments, especially at a salt concentration of 300 nM.